The Role of Extracurricular, Co-curricular, and Curricular Activities in the Development of Talent Interests of Elementary School Students - Herdianti, Riza Alifia; Zahra, Savina Aqila; Firdausi, Novita; Zhafira, Nurul; Kurniawan, Machful Indra (Universitas Muhammadiyah Sidoarjo, 2024)
This article reviews the role of extracurricular, co-curricular, and curricular activities in supporting the development of students' interests and talents at SD Muhammadiyah 1 Gempol. The development of students' interests and talents is considered to play an important role in shaping their character and developing their academic abilities. This study used a descriptive qualitative approach with observation, interview and data collection methods. This article is assembled based on a literature review as well as data analysis to find out the results of these activities contributing to the development of students' interests and talents.